2022
DOI: 10.3390/biology11121718
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Indoxacarb Resistance in the Fall Armyworm: Selection, Inheritance, Cross-Resistance, Possible Biochemical Mechanisms, and Fitness Costs

Abstract: The fall armyworm, Spodoptera frugiperda (J.E. Smith), is a voracious insect pest that is difficult to control due to resistance to insecticides and Bt proteins. We assessed cross-resistance, resistance mechanism, and fitness costs based on the life history traits of S. frugiperda. We established an S. frugiperda strain selected for resistance to indoxacarb (Ind-SEL) from a field-collected population and an unselected strain, Ind-UNSEL. Results indicated that after 24 generations of selection, the resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…It could be attributed to the fact that the potential cross-resistance between fluxametamide and emamectin benzoate in the fluxametamide-selected strain of FAW was a possible resultant effect of a similar detoxification mechanism concerning elevated GST activities. The involvement of P450 in the indoxacarb resistance [65] and GST in the resistance to synthetic pyrethroid insecticides [71] in FAW have been reported by previous workers. In this study, the activities of detoxification enzymes were mild in fluxametamide-selected generations of FAW; we speculate that the limited resistance development rate is correlated with the slow metabolic detoxification process.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…It could be attributed to the fact that the potential cross-resistance between fluxametamide and emamectin benzoate in the fluxametamide-selected strain of FAW was a possible resultant effect of a similar detoxification mechanism concerning elevated GST activities. The involvement of P450 in the indoxacarb resistance [65] and GST in the resistance to synthetic pyrethroid insecticides [71] in FAW have been reported by previous workers. In this study, the activities of detoxification enzymes were mild in fluxametamide-selected generations of FAW; we speculate that the limited resistance development rate is correlated with the slow metabolic detoxification process.…”
Section: Discussionsupporting
confidence: 65%
“…It might be attributed to the fact that fluxametamide has shown an asymmetric nature of cross-resistance with emamectin benzoate, which is an example of a sudden unpredictable phenomenon [61,62]. Several cases of cross-resistance between Cry1 proteins [63], spinosad and spinetoram [64], indoxacarb, and deltamethrin [65] in FAW have already been reported previously. Roy et al [32] investigated a similar type of cross-resistance pattern between fluxametamide and emamectin benzoate in P. xylostella, another invasive lepidopteran insect pest.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Evaluation of fitness and stability in selected populations has a high level of practical importance for determining resistance risk associated with the use of insecticides and can be useful for formulating insecticide resistance management strategies (Carrière and Tabashnik 2001, 2023). Recent studies of indoxacarb resistant noctuid populations showed significantly slower growth and development, and lower fecundity in S. frugiperda (Hafeez et al 2022b) and H. armigera (Cui et al 2018) suggesting the presence of indoxacarb resistance genes in these populations was deleterious. In the present study a lack of stability in a heterogeneous population of the UN1U3-10 strain resulted in a decline in resistance ratio from 313-fold to 53-fold after the strain had been reared for 6 generations in the absence of selection, indicating that a fitness cost may be associated with the allele(s) that confer resistance in the UN1U3-10 strain, the effects of which cumulate over multiple generations causing an overall decline in the number of resistant individuals in the population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cytochrome P450 (CYP450), glutathione S -transferases (GSTs), and carboxylesterases (CAREs) of insects are known to be central to pesticide metabolism and resistance. Inhibitors of the above detoxifying enzymes, such as triphenyl phosphate (TPP), diethyl maleate (DEM), and piperonyl butoxide (PBO), could be used to attenuate the pesticide resistance in insects. , P. xylostella GSSs were identified as a specific protective strategy to cope with host plant defense compounds, while the function of GSSs in the metabolism of conventional pesticides has not been reported, as far as we know.…”
Section: Discussionmentioning
confidence: 99%